Peran Komitmen dan Komunikasi dalam Long Distance Relationship: Sebuah Studi Literatur - Eko Joko Nugroho; Mulya Virgonita I. Winta; Margaretha Maria Shinta Pratiwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study explores the role of commitment and communication in long-distance relationships (LDR), focusing on their influence on relationship quality and partner satisfaction. Employing a descriptive and analytical literature review approach, the study synthesizes findings from relevant studies published between 2021 and 2025. Results reveal that strong emotional commitment, supported by open and effective communication, plays a crucial role in sustaining long-term relationship stability. Additionally, factors such as trust, emotional support, and the strategic use of communication technology significantly enhance emotional bonds and overall satisfaction. These insights offer valuable guidance for couples in LDRs to develop adaptive communication and commitment strategies in navigating physical distance.